2020
DOI: 10.7554/elife.59177
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic model and therapeutic interventions for COVID-19 involving a RAS-mediated bradykinin storm

Abstract: Neither the disease mechanism nor treatments for COVID-19 are currently known. Here we present a novel molecular mechanism for COVID-19 that provides therapeutic intervention points that can be addressed with existing FDA-approved pharmaceuticals. The entry point for the virus is ACE2, which is a component of the counteracting hypotensive axis of RAS, that produces the nonapeptide angiotensin1-9 from angiotensin I. Bradykinin is a potent, but often forgotten, part of the vasopressor system that induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
449
0
29

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 353 publications
(490 citation statements)
references
References 84 publications
12
449
0
29
Order By: Relevance
“…The size of the nodes and weight of the edges is associated with Rank X score, related to biological importance, while color is associated with Rank Delta, related to the difference in co-expression network between control and disease. Notice that ACE2 shows a reduced number of connections, consistent with its initial downregulation in the early stage of infection; in later stages of infection, we can expect an inversion of observed regulation caused by the virus-relatedACE2 overexpression [40].…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The size of the nodes and weight of the edges is associated with Rank X score, related to biological importance, while color is associated with Rank Delta, related to the difference in co-expression network between control and disease. Notice that ACE2 shows a reduced number of connections, consistent with its initial downregulation in the early stage of infection; in later stages of infection, we can expect an inversion of observed regulation caused by the virus-relatedACE2 overexpression [40].…”
Section: Resultsmentioning
confidence: 84%
“…After the virus enters the cells, ACE2 is likely to decrease its activity, thus favoring an increase of the ACE/ACE2 balance toward the prevalence of ACE arm in the RAS which causes an increase of ROS production, vasoconstriction, and inflammation [71]. On the other hand, a recent COVID-19 related study showed decreased expression of ACE in combination with increases in ACE2 likely causing bradykinin-related increases in vascular dilation, vascular permeability and hypotension explaining many of the symptoms being observed in COVID-19 [40].…”
Section: Discussionmentioning
confidence: 99%
“…ACE-2 was shown to be involved with SARS-CoV-2 human infection ; the ectodomain of the S protein of SARS-CoV binds to the peptidase domain of ACE2 with relatively high a nity 21 . In cells of patients with severe symptoms of COVID-19, ACE2 was substantially upregulated 199 fold; this upregulation was suggested to be one of the factors leading to disruption of the renin-angiotensin system 22 . The ability of F CBD to reduce ACE2 expression is important concerning treatment of COVID-19 patients, yet should be considered with care as the advantages and disadvantages of ACE2 expression reduction are disputed 20 .…”
Section: Discussionmentioning
confidence: 98%
“…More effective mitigation measures should focus on safeguarding the population above 65 years of age to reduce mortality substantially and efficiently (14). These measures should emphasize distancing, isolation, technological medical monitoring and connections, and assure that the elderly are receiving the correct nutritional supplementation, including monitoring their vitamin D levels to ensure blood levels are at or above 50 ng/ml (25,26,27,28).…”
Section: Discussionmentioning
confidence: 99%